Exposure of nanoplastics to freeze-thaw leads to aggregation and reduced transport in model groundwater environments. (1st February 2021) - Alimi, Olubukola S.; Farner, Jeffrey M.; Tufenkji, Nathalie
Highlights: First report on the effect of freeze-thaw on the fate of nanoplastics. Nanoplastics exposed to freeze-thaw formed aggregates and were less mobile. Natural organic matter increased particle mobility but did not prevent aggregation. The nanoplastic aggregates were not prone to disaggregation. Climate and temperature changes can impact plastic exposure risks. Abstract: Despite plastic pollution being a significant environmental concern, the impact of environmental conditions such as temperature cycling on the fate of nanoplastics in cold climates remains unknown. To better understand nanoplastic mobility in subsurface environments following freezing and thawing cycles, the transport of 28 nm polystyrene nanoplastics exposed to either constant (10°C) temperature or freeze-thaw (FT) cycles (-10°C to 10°C) was investigated in saturated quartz sand. The stability and transport of nanoplastic suspensions were examined both in the presence and absence of natural organic matter (NOM) over a range of ionic strengths (3-100 mM NaCl). Exposure to 10 FT cycles consistently led to significant aggregation and reduced mobility compared to nanoplastics held at 10°C, especially at low ionic strengths in the absence of NOM. While NOM increased nanoplastic mobility, it did not prevent the aggregation of nanoplastics exposed to FT. We compare our findings with existing literature and show that nanoplastics will largely aggregate and associate with soils rather than undergo long range transport in groundwater in colder climates following freezing temperatures. In fact, FT exposure leads to the formation of stable aggregates that are not prone to disaggregation. As one of the first studies to examine the coupled effect of cold temperature and NOM, this work highlights the need to account for climate and temperature changes when assessing the risks associated with nanoplastic release in aquatic systems. Graphical abstract: Image, graphical abstract